Correlation of Fried Snacks Intake with Free Radicals and Obesity in Elementary School Children - Ummi Hidayati; Albiner Siagian; Etti Sudaryati (Budapest International Research in Exact Sciences (BirEx) Journal, 2020)
The increase in degenerative disease and obesity is mainly caused by lifestyle, eating pattern, and activities. Obesity can cause death throughout the world. It affected 349 million children and adolescents (5-19 years old) in 2016. The objective of this research was to find out the correlation of fried snacks intake with free radicals, and obesity. The research used quantitative method with cross sectional design. The samples were 56 students of elementary school, taken by using purposive sampling technique. The result of the research showed that 50 students (84.7%) had normal free radicals in their bodies and 9 students (15.3%) had high free radicals. There were 11 students (18.6%) who were obese and 48 students (81.4%) were not. The result of pearson correlation test showed that there was significant correlation of the number of energy, carbohydrates, fat contribution in fried snacks with free radical content (MDA analysis) at respective p-value of 0.004, 0.005, and 0.026. The result of correlation test showed that there was the correlation between fat nutrient intake in fried snacks and obesity (p=0.012). Reducing consuming fried snacks is one of the ways to decrease the effect of free radicals in school children’s bodies.